PROBLEMS OF LEGAL REGULATION OF THE USE OF POLYGRAPH IN THE SECURITY AND DEFENSE SECTOR OF UKRAINE - Kazmiruk, S.; Pampukha, I.; Blyzniuk, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The year 2021 was proclaimed the year of the Euro-Atlantic transformation at the Department of Defense of Ukraine. The result of such transformational processes in the DoD of Ukraine and the Armed Forces of Ukraine will be the creation of the integrated Euro-Atlantic type defense institution that will ensure their obligatory transformation, together with the other subjects of the security and defense sector of Ukraine to the new standards functioning and the command and control procedure. In particular, the introduction of legal regulation of the use of the polygraph. Military security is one of the fundamental requirements to implement the right of the people of Ukraine on self-identification, preserve Ukraine as a state and secure its sustainable development. The protection of the sovereignty and territorial integrity of Ukraine is the utmost valuable function of the State. The fulfillment of this norm of the Constitution of Ukraine in terms of existential military threat to national security requires applying a number of measures and defensive actions that adhere to the principles and norms of international law. The main purpose of the Strategy of the military security of Ukraine is a preliminary prepared and comprehensively maintained all-encompassing defense of Ukraine based on the principles of deterrence, sustainability, and cooperation that ensures military security, sovereignty, and territorial integrity of the state by introducing innovative tools to detect hidden information. In the course of the Euro-Atlantic integration process, there is a critical moment to start carrying out specific, complex, and relevant tasks in the sphere of external political activity that facilitate the implementation of relevant directions in developing innovative systems aimed at identifying concealed and false information. Particularly, the linguistic support of events of defense and military cooperation in order to systematically implement the reforms of the security and defense sector that are directed to meet the international NATO-members' standards. It is also relevant to urgently implement the legal and ethical norms on the activity of the polygraph examiner's when performing a psychophysiological detection of deception using a polygraph.
Keywords: military security, all-encompassing defense, NATO, legal regulation, psychophysiological detection of deception, polygraph, polygraph examiner, linguistic component, code of ethics, training